ORGANIC FOOD - PRO ET CONTRA - Ristić, Nebojša; Malićević, Sead (Sport - nauka i praksa, 2023)
Based on all available information, there has been a great expansion of organic food production and sale, both globally and in Serbia. It is estimated that this expansion results from buyers’ belief that organic food is tastier and/or healthier, more nutritious, that it contains less pesticides, preservatives, additives, thaat it does not contain any genetically modified components, etc. However, which of these beliefs are facts, and which are misconceptions? In the absence of studies dealing with the issue of organic food in Serbia, we rely on the results of studies conducted in the world, primarily in countries where the production and sale of organic food has a decades-long tradition. Most studies covered by this review refer to the presence of pesticides in organic food and they all unequivocally established that organic food contains significantly lower amounts of pesticides than conventionally produced food. In terms of other aspects of health safety, it was found that organic food has significantly lower values or absence of antibiotics, growth hormones and factors, genetically modified components as well as artificial preservatives and additives. Some of the research that was conducted to confirm the claim that organic food is more nutritious than conventionally produced food, established that some foods have more vitamins, minerals and antioxidants. However, numerous studies did not confirm these conclusions, but rather found that there is no significant difference between the content of the mentioned ingredients in organic and conventional food. Which of the above is true will be confirmed by some future, fully objective studies.